The relationship between anger expression and imagery vividness: the mediating effect of resilience in Korean martial art - Di Corrado, D.; Buscemi, A.; Parisi, M. C.; Zoffoli, A.; La Paglia, R.; Coco, M. (Sport Sciences for Health, 2025)
Purpose Taekwondo has a rich history that dates back to ancient Korea. It promotes discipline, respect, and physical fitness. This study aimed to investigate the mediating role of resilience in the relationship between static and dynamic vividness, and the degree of anger expression, in a group of 100 taekwondo athletes (57 males and 43 females), aged between 18 and 23 years (M = 20.6, SD = 2.05).